Brain tissue oxygen monitoring and hyperoxic treatment in patients with traumatic brain injury - Beynon, Christopher; Kiening, Karl; Orakcioglu, Berk; Unterberg, Andreas; Sakowitz, Oliver (Journal of neurotrauma, 2012)
Cerebral ischemia is a well-recognized contributor to high morbidity and mortality after traumatic brain injury (TBI). Standard of care treatment aims to maintain a sufficient oxygen supply to the brain by avoiding increased intracranial pressure (ICP) and ensuring a sufficient cerebral perfusion pressure (CPP). Devices allowing direct assessment of brain tissue oxygenation have showed promising results in clinical studies, and their use was implemented in the Brain Trauma Foundation Guidelines for the treatment of TBI patients in 2007. Results of several studies suggest that a brain tissue oxygen-directed therapy guided by these monitors may contribute to reduced mortality and improved outcome of TBI patients. Whether increasing the oxygen supply to supraphysiological levels has beneficial or detrimental effects on TBI patients has been a matter of debate for decades. The results of trials of hyperbaric oxygenation (HBO) have failed to show a benefit, but renewed interest in normobaric hyperoxia (NBO) in the treatment of TBI patients has emerged in recent years. With the increased availability of advanced neuromonitoring devices such as brain tissue oxygen monitors, it was shown that some patients might benefit from this therapeutic approach. In this article, we review the pathophysiological rationale and technical modalities of brain tissue oxygen monitors, as well as its use in studies of brain tissue oxygen-directed therapy. Furthermore, we analyze hyperoxia as a treatment option in TBI patients, summarize the results of clinical trials, and give insights into the recent findings of hyperoxic effects on cerebral metabolism after TBI.
Published online:13 Aug 2012
Gesehen am 18.06.2018